Transformasi Budaya Lokal Dalam Era Digital: Analisis Praktik Etika Kreator Konten Di Makassar - Zulkarnain Hamson; Muhammad Akbar; Syamsuddin Aziz (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
The digital era has brought significant changes in the way local culture is represented and consumed, including in Makassar. Content creators play an important role in packaging and disseminating cultural values through various digital platforms. This study analyzes the transformation of local culture in the digital era and the ethical practices applied by content creators in Makassar. With a qualitative approach, this study uses a case study method through interviews with five content creators, namely: Tuming Abu, Doyok Jarot, Nojeng Comol, Bassi Toayya and Rijal Jamal. Observation, and analysis of digital content from various social media platforms owned by the five creators. The results of the study show that digitalization has facilitated access to local culture, but also presents ethical challenges such as cultural commodification, distortion of traditional values, and lack of attribution to cultural heritage. Some creators have applied ethical principles such as originality, respect for cultural values, and education for the audience, but there are still practices that do not consider ethical aspects. This study recommends ethical guidelines for content creators and the active role of the government and community in maintaining the authenticity of local culture in the digital era.